E. coli Meningitis Presenting in a Patient with Disseminated Strongyloides stercoralis - Juliana B. Gomez; Yvan Maque; Manuel A. Moquillaza; William E. Anicama (Case Reports in Infectious Diseases)
Introduction. Spontaneous Escherichia coli meningitis is an infrequent condition in adults and is associated with some predisposing factors, including severe Strongyloides stercoralis (SS) infections. Case Presentation. A 43-year-old Hispanic man, with history of travelling to the jungle regions of Peru and Brazil two decades ago, and who received prednisone due to Bell’s palsy for three weeks before admission, presented to the Emergency Department with diarrhea, fever, and hematochezia. A week after admission he developed drowsiness, meningeal signs, abdominal distension, and constipation. A cerebrospinal fluid culture showed extended spectrum β-lactamase producing E. coli. A colonoscopy was performed and showed pancolitis. Three days after the procedure the patient became unstable and developed peritoneal signs. He underwent a laparotomy, which ended up in a total colectomy and partial proctectomy due to toxic megacolon. Three days later the patient died in the intensive care unit due to septic shock. Autopsy was performed and microscopic examination revealed the presence of multiple Strongyloides larvae throughout the body. Conclusion. Strongyloides stercoralis infection should be excluded in adults with spontaneous E. coli meningitis, especially, if gastrointestinal symptoms and history of travelling to an endemic area are present. Even with a proper diagnosis and management, disseminated strongyloidiasis has a poor prognosis.